Welcome, caller, this is Chloe - Coriell, Shelley (Amulet, 2012)
"When big-hearted Chloe Camden's best friend shreds her reputation and her school counselor axes her junior independent study project, Chloe is forced to take on a 'more meaningful' project by joining her school's struggling radio station"-- |c Provided by publisher.